Tragedy - Valency, Maurice (Rowman & Littlefield Publishers, 1998)
This introduction to Greek tragedy, the origin of much of our modern drama, is the work of a remarkable scholar who is also a practical man of theater. The author of magisterial studies of Ibsen, Strindberg, Chekhov and Shaw, and of symbolism in the theater from the nineteenth century to our times, Maurice Valency has written for the stage and for television, and he translated, adapted and collaborated in producing two great Broadway successes–Giraudoux's the Mad Woman of Chaillot and Durrenmatt's The Visit.